The significance of clutch-size in waterfowl - Lack, David (Wildfowl, 1967)
1. The average clutch-size of the different species of waterfowl varies inversely with the relative size of the egg. This applies to the Anatidae as a whole, to each of the four genera which can be tested separately, and to four subspecies of the Mallard. 2. It is suggested that the average clutch of each species has been evolved in relation to the average availability of food for the female around the time of laying, modified by the relative size of the egg. 3. The specific differences in clutch-size and egg-size are mainly hereditary and variations in the food supply for a particular female perhaps influence mainly the date of laying. 4. The inverse relationship between clutch-size and egg-size is only broad, probably because the average availability of food differs greatly in different species. 5. The advantage of a relatively large egg is that the newly hatched chick has a relatively large reserve of food.